STUDI PERTUMBUHAN BIBIT RUMPUT LAUT (Kappaphycus alvarezii) HASIL KULTUR JARINGAN DENGAN METODE LONGLINE BERBINGKAI DI BALAI BESAR PERIKANAN BUDIDAYA LAUT LAMPUNG - Suci Rachmawati; Annur Ahadi Abdillah (Jurnal Perikanan Pantura (JPP), 2019)
Seaweed is one of the important commodities of fishery products that have economic value. Farmers often use repetitive seeds from the same broodstock so that they have the potential to experience a decline in quality. So it is necessary to do a study of seaweed cultivation using tissue culture seedling with the long line method as an effort to develop seaweed farming. Seaweed (Kappaphycuz alvarezii) has an absolute growth of 138.61 grams, with a growth rate of 4.85%. The growth of seaweed from tissue culture seedlings is better than the growth of conventional seedlings.